Female stereotypes in the novel The Agüero Sisters by Cristina García - Martínez, Mariana Estela (2015)
The aim of this work is to explore the construction of Latino women stereotypes through the choice of vocabulary in the nov,I The Agüero Sisters by Cristina García . Lexical choices were selected and analyzed on r basis of Cultural Studies and Critica Linguistics. Our results mainly revealed the objectification and animalization of women with idealized bodies and relaxed attitudes tof ards their sexual life, which make men fall under their powerful spell.